Housing policies: recent developments in the peruvian economy - Esteves, Cecilia (2004)
This work explains the recent evolution of housing policies in Peru and, on this basis, analyses the development of the residential real estate sector during the last five years, considering the financial and institutional factors that have led it. The first section describes the housing deficit of the country and gives an account of the previous housing policies and the context in which the MiVivienda Fund arises. The second section describes the housing production chain and the role of the aforementioned fund. Finally, the third section is devoted to the analysis of housing policies and, particularly, to the financing programs that the current government has implemented to convert the poorest population into homeowners. Finally, the document closes with recommendations on what should be done to maintain the achievements.